Isothermal microcalorimetry minimal inhibitory concentration testing in extensively drug resistant Gram-negative bacilli: a multicentre study. (October 2020) - Tellapragada, C.; Hasan, B.; Antonelli, A.; Maruri, A.; de Vogel, C.; Gijón, D.; Coppi, M.; Verbon, A.; van Wamel, W.; Rossolini, G.M.; Cantón, R.; Giske, C.G.
Abstract: Objectives: To evaluate the performance of an isothermal microcalorimetry (IMC) method for determining the MICs among extensively drug-resistant Gram-negative bacilli. Methods: A collection of 320 clinical isolates ( n  = 80 of each) of Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa and Acinetobacter baumannii from Sweden, Spain, Italy and the Netherlands were tested. The MICs were determined using the IMC device calScreener (Symcel, Stockholm, Sweden) and ISO-broth microdilution as the reference method. Essential agreement, categorical agreement, very major errors (VME), major errors (ME) and minor (mE) errors for each antibiotic were determined. Results: Data from 316 isolates were evaluated. Four errors (two ME, one VME, one mE) among 80 K. pneumoniae, six errors (four ME, one VME, one mE) among 79 E. coli, 15 errors (seven VME, three ME, five mE) among 77 P. aeruginosa and 18 errors (12 VME, two ME, four mE) among 80 A. baumannii were observed. Average essential agreement and categorical agreement of the IMC method were 96.6% (95% confidence interval, 94.2–99) and 97.1% (95% confidence interval, 95.4–98.5) respectively when the MICs were determined at the end of 18 hours. Categorical agreement of the IMC method for prediction of MIC by the end of 8 hours for colistin, meropenem, amikacin, ciprofloxacin and piperacillin/tazobactam were 95%, 91.4%, 94%, 95.2% and 93.7% respectively. Conclusions: The IMC method could accurately determine the MICs among extensively drug-resistant clinical isolates of E. coli, K. pneumoniae, P. aeruginosa and A. baumannii isolates.